2012
DOI: 10.1021/jf301926w
|View full text |Cite
|
Sign up to set email alerts
|

Bowman-Birk and Kunitz Protease Inhibitors among Antinutrients and Bioactives Modified by Germination and Hydrolysis in Brazilian Soybean Cultivar BRS 133

Abstract: Soybean contains constituents that have antinutritional and bioactive properties. Enzymatic hydrolysis and germination can enhance the biological activity of these compounds in soybean. The objective of this study was to investigate the effect of germination, Alcalase (protease) hydrolysis, and their combination on the concentrations of antinutritional and bioactive compounds in Brazilian soybean cultivar BRS 133. A combination of germination and Alcalase hydrolysis resulted in the degradation of Bowman-Birk i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 37 publications
1
21
0
1
Order By: Relevance
“…Previous studies have shown that processing could lead to reduction in the concentrations of BBI and KTI. Heat-induced protein aggregation led to reduction in KTI and BBI in soymilk (Chen, Xu, Zhang, Kong & Hua, 2014) while germination and hydrolysis led to modification of these protease inhibitors (Dia, Gomez, Vernaza, Berhow, Chang & de Mejia, 2012). As expected, pepsin and pepsin-pancreatin hydrolysis led to reduction in the concentration of these bioactive peptides (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that processing could lead to reduction in the concentrations of BBI and KTI. Heat-induced protein aggregation led to reduction in KTI and BBI in soymilk (Chen, Xu, Zhang, Kong & Hua, 2014) while germination and hydrolysis led to modification of these protease inhibitors (Dia, Gomez, Vernaza, Berhow, Chang & de Mejia, 2012). As expected, pepsin and pepsin-pancreatin hydrolysis led to reduction in the concentration of these bioactive peptides (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…However, a number of genes whose protein products are not agronomically desirable due to their anti-nutritional effect are expressed in high quantities as well. Among those are genes encoding for protease inhibitors including Bowman-Birk serine protease inhibitors and Kunitz trypsin inhibitors that hamper the digestion of soybean proteins in animals and humans [52-54], and the lipoxygenases involved in oxidation of polyunsaturated fatty acids, which add unpleasant flavors to soybean products [33]. Many of the above mentioned genes show expression variation among the nine lines.…”
Section: Discussionmentioning
confidence: 99%
“…Bowman Birk and Kunitz inhibitors are trypsin/chymotrypsin inhibitors, which reduce the breakdown of proteins during digestion; α-amylase inhibitor reduces the breakdown of carbohydrates during digestion. Several studies demonstrated that legume germination is able to decrease the concentration of these anti-nutritional compounds (Aguilera et al, 2013;Dia, Gomez, Vernaza, Berhow, Chang, & de Mejia, 2012;Paucar-Menacho, Berhow, Gontijo-Mandarino, Chang, & de Mejia, 2010;Vidal-Valverde, Frias, Sierra, Blazquez, Lambein, & Kuo, 2002). The concentration of Bowman-Birk inhibitor in the non-germinated and non-hydrolyzed sample (G0-0h) was 6.6 mg/g of SP.…”
Section: Proteases and α-Amylase Inhibitorsmentioning
confidence: 99%